Embracing Multiliteracies Challenges: Navigating Multimodal Literacy in Maritime Vocational Education with the New London Group Framework - Azizah, Shofie Nurul; Triastuti, Anita (Formosa Journal of Sustainable Research, 2024)
In the context of rapidly evolving digital technology and diverse communication modalities, English for Specific Purposes (ESP) instructors must adapt their pedagogical strategies to meet the literacy needs of ESP students. This study, grounded in the multiliteracies framework by the New London Group (1996), examines the challenges faced by a teacher in integrating various communication modes—verbal, visual, gestural, spatial, and multimodal digital texts—within the curriculum of a maritime vocational high school in Indonesia. Utilizing a qualitative case study approach, data were collected through classroom observations and interviews, analyzed via thematic analysis. Findings reveal four significant challenges in implementing multiliteracies pedagogy, contributing to discussions on literacy education and the impact of digital technology in educational settings